Transition to a new global paradigm of development and the role of the united nations in this process. Issue 8 (17th November 2017) - Bondarenko, Valentina M.; Ilyin, Ilya V.; Korotayev, Andrey V.
Abstract : In his2011 article "Global Bifurcation: The Decision Window" Ervin Laszlo notes that "we have reached a watershed in our social and cultural evolution. The sciences of systems tell us that when complex open systems … approach a condition of critical instability, they face a moment of truth: they either transform or break down." (p. 108) In this article we provide our own vision of this Global Bifurcation. This work stems naturally from the research highlighted in the article titled "Transition to Crisis-Free Development: A Myth or Reality?" that was published in World Futures (Bondarenko, 2014a ). In our new article, we move forward suggesting that crises-free development is not only possible but is also very likely, and paradoxically the world is now going through the most challenging transition from one paradigm of development to another. Based on our previous research as well as the findings of the Fifth Report to the Club of Rome, we suggest reasons for the development and implementation of a megaproject featuring a new model of life so as to make the paradigm shift possible, exclude negative implications of the upcoming technological "singularity, " and foster the achievement of an objectively defined goal of development, and this should reasonably require support from and direct involvement of the United Nations. The mechanism for implementation of this model suggests coordinating interests of the government, society, and business communities on each level with interests of particular individuals.